Radiation-induced solute segregation in metallic alloys. Issue 3 (June 2016) - Ardell, Alan J.; Bellon, Pascal
Highlights: The history of RIS is covered in great detail, both experimentally and theoretically. We emphasize advances in understanding diffusion in concentrated solid solutions. We highlight GB structure and its detailed relationship to point-defect sink strength. The impact of APT on evaluating and modeling RIS at GBs and dislocations is featured. We spotlight the role of self-organization on defect-formation involving RIS. Abstract: The subject of radiation-induced solute segregation (RIS) in metallic alloys is reviewed. RIS manifests itself in several different ways, including diffusion to point-defect sinks (dislocations, grain boundaries, voids, etc.), which can induce precipitation in undersaturated alloys, as well as self-organization of solute clusters and precipitation in defect-free material. Diffusion in dilute and concentrated alloys is highlighted, as are theories of RIS that include new ideas on diffusion of complexes involving coupling between fluxes of point defects and of solute atoms. Many important experimental observations are presented, including up-to-date findings using atom-probe tomography, with special emphasis on solute segregation in austenitic and ferritic steels. Results from computational modeling and theory are also presented and discussed in light of experimental findings. Examples illustrating the factors affecting RIS are shown and some important outstanding issues that impact the current understanding of RIS are described and discussed.